IRS LISS3-based study of spatio-temporal land use and land cover changes and their relationship with the Ahiran watershed of Hasdeo River in Central India - Singh, S.S; Singh, Ankita (Indian Forester, 2022)
The Hasdeo River watershed is the source of various land use practices. Human activities have a long-term impact on land use/cover changes and the sustainability of a watershed to research aims to assess changes in land use/land cover (LULC) in the Ahiran subwatershed of the Hasdeo River in Central India, based on temporal analysis of independently produced classified images, Normalized Difference Vegetation Index (NDVI), and Principal Component Analysis (PCA) from 2000 to 2013. The comparison of the LULC change maps over different time periods (2000-2013) shows that the land use structures within the study region have changed. The land use intensity within the study region indicates the degree of human activities on the lands, which may be important indicators of land use pattern. During the thirteen years, the dense forest region rise is hyperbolic due to the establishment of plantations and other tree species in barren and scrublands. Expansion of mining, industrial activities, and settlements has to hydrological changes also. The NDVI and SAVI indicate of healthy and unhealthy vegetation in subwatersheds when compared to various LULC. PCA demonstrates a strong relationship between barren land and riverbed, water resources, and dense forest to conclude, subwatershed is currently due to intensive anthropogenic activities. Good government policies which encourage the growth of forests in the vicinity of mining areas through social forestry should be implemented.